2018
DOI: 10.1017/s1355770x18000463
|View full text |Cite
|
Sign up to set email alerts
|

Economic development and residential water consumption in Chile

Abstract: A better understanding of the relative importance of factors related to climate change and to changes associated with economic growth would serve to inform water policy and to focus scarce public resources on anticipated problems arising from distinct sources of changes in water demand. This article investigates the determinants of residential water consumption in Chile, a developing country that has seen noteworthy changes in incomes, household size, poverty rates and levels of urbanization, and which is proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In their survey, household size was negatively correlated with per capita water use. Fercovic et al (2019) similarly found that while total domestic water consumption increased per household as household size increased, the per capita water use decreased, consistent with a household economy of scale. Keshavarzi et al (2006) also found that the age of the head of household was positively correlated with per capita water use, households with younger families used less water per capita.…”
Section: Size Of Householdmentioning
confidence: 62%
“…In their survey, household size was negatively correlated with per capita water use. Fercovic et al (2019) similarly found that while total domestic water consumption increased per household as household size increased, the per capita water use decreased, consistent with a household economy of scale. Keshavarzi et al (2006) also found that the age of the head of household was positively correlated with per capita water use, households with younger families used less water per capita.…”
Section: Size Of Householdmentioning
confidence: 62%
“…On the other hand, 15 countries in LAC present more than 20,000 m 3 per inhabitant per year of total renewable water resources [7]. Various factors, such as the level of development of the countries, the level of industrialization, urbanization, or poverty, influence water consumption and the uses that it is given [40,41]. Figure 1 shows the proportion of water destined for different uses (agricultural, industrial, and municipal) in the different regions of the world.…”
Section: Water Resources In the Worldmentioning
confidence: 99%
“…At the same time, per capita income is a major factor that affects water consumption. Studies have also shown that water consumption is strongly related to the level of economic development (Fercovic et al, 2019). Sauri (2019) has studied the driving factors of the significant decline in water consumption in some major Spanish cities between 2003 and 2016.…”
Section: Literature Review and Research Gapmentioning
confidence: 99%